2020
DOI: 10.3390/rs12030481
|View full text |Cite
|
Sign up to set email alerts
|

The Precipitation Inferred from Soil Moisture (PrISM) Near Real-Time Rainfall Product: Evaluation and Comparison

Abstract: Near real-time precipitation is essential to many applications. In Africa, the lack of dense rain-gauge networks and ground weather radars makes the use of satellite precipitation products unavoidable. Despite major progresses in estimating precipitation rate from remote sensing measurements over the past decades, satellite precipitation products still suffer from quantitative uncertainties and biases compared to ground data. Consequently, almost all precipitation products are provided in two modes: a real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…GPM+SM2RAIN ( https://zenodo.org/record/3345323 ) has a spatial resolution of 0.25° and daily temporal resolution. Two PRISM-based satellite rainfall products have been considered 15 , 36 . The PRISM method is applied to correct GPM-ER with SMOS (PRISM-SMOS) and SMAP (PRISM-SMAP) soil moisture observations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GPM+SM2RAIN ( https://zenodo.org/record/3345323 ) has a spatial resolution of 0.25° and daily temporal resolution. Two PRISM-based satellite rainfall products have been considered 15 , 36 . The PRISM method is applied to correct GPM-ER with SMOS (PRISM-SMOS) and SMAP (PRISM-SMAP) soil moisture observations.…”
Section: Methodsmentioning
confidence: 99%
“…PRISM-SMOS and PRISM-SMAP have a spatial resolution of 0.25° and 3-h temporal resolution. Details on the characteristic of GPM+SM2RAIN algorithm and on PRISM approach is given in 11 , 36 and we refer the interested reader to these publications for more specific information. Here, briefly, we underline the main difference between the two approaches that relies on the method used for integrating soil moisture observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In semi-arid regions, the issue of soil moisture becomes very important since moisture stress in crop is one of the key determinants of crop failure. In other studies, Pellarin et al (2020) has shown that soil moisture content can be used to infer precipitation using PrISM Model. This kind of modeling is said to provide useful information concerning crop yield estimates and irrigation demands over large areas.…”
Section: Precipitation Amount Rate and Soil Moisture Variationsmentioning
confidence: 99%
“…There has been increasing interest in the application of satellite precipitation products over East African regions of data scarcity (Näschen et al 2018;Oduor et al 2020;Pellarin et al 2020). A majority of the studies have focused around the greater Lake Victoria drainage basin considering its economic significance (Habib et al 2012;Williams et al 2015;Awange, 2021).…”
Section: Introductionmentioning
confidence: 99%